2021
DOI: 10.1021/acsami.1c08218
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired, Cholesteric Liquid-Crystal Reflectors with Time-Controlled Coexisting Chiral and Achiral Structures

Abstract: The twisted structures of the chitin-based cuticle of beetles confer specific optical characteristics on them. Intrigued by the observation of Bragg gratings with a depth-dependent periodicity in the cuticle of Chrysina beetles, we determine the experimental conditions leading to their transcription into cholesteric liquid-crystal oligomers. We correlate the optical properties of reflectors thus produced with their internal morphology, as observed by transmission electron microscopy. With the use of a single p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…It was reported that the isomerization of CA was time-dependent under UV light . Therefore, the structural colors of LC242/CA mixtures in the cholesteric phase should be also irradiation time-dependent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It was reported that the isomerization of CA was time-dependent under UV light . Therefore, the structural colors of LC242/CA mixtures in the cholesteric phase should be also irradiation time-dependent.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the isomerization of CA was timedependent under UV light. 37 Therefore, the structural colors of LC242/CA mixtures in the cholesteric phase should be also irradiation time-dependent. To reveal this irradiation time dependency behavior, an LC242/CA mixture at a weight ratio of 94/6 was irradiated under a low-pressure Hg lamp (80 W) at a distance of 5 cm and 80 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liquid crystals (LCs) have been the star materials in the past decades due to the subtle integration of the molecular ordering and fluidity. [1][2][3] Since the first observation of liquid crystalline behavior by Reinitzer in 1888, the research on these strange and fascinating materials has gathered wide attention. [4,5] Based on the phase-transition condition, the LCs are classified into two types including thermotropic LCs and lyotropic LCs.…”
Section: Introductionmentioning
confidence: 99%